Rozwiązane

Rozwiąż równanie.

1. [tex]\frac{x}{3}[/tex] - 2 = 2x - [tex]\frac{x+3}{6}[/tex]
2. [tex]\frac{2}{5}[/tex] x - 0,4 = 2 (0,75 - [tex]\frac{1}{5}[/tex] x) + 0,1
3. [tex]\frac{1}{3}[/tex] ([tex]x^{2}[/tex] + x) + [tex]\frac{2}{3}[/tex] = 2 ( [tex]\frac{2}{3}[/tex] - 2x) + 11 + [tex]\frac{1}{3} x^{2}[/tex]


Proszę daje najjj



Odpowiedź :

Odpowiedź:

1. [tex]\frac{x}{3} - 2 = 2x - \frac{x+3}{6}[/tex]  / *6

2x-12=12x-(x+3)

2x-12=12x-x-3

2x-12=11x-3

2x-11x=12-3

-9x=9

-x=1

x=-1

2. [tex]\frac{2}{5}[/tex] x - 0,4 = 2 (0,75 - [tex]\frac{1}{5}[/tex]x) + 0,1

[tex]\frac{2}{5} x - \frac{2}{5} =2(\frac{3}{4} - \frac{1}{5} x)+ \frac{1}{10}[/tex]

[tex]\frac{2}{5}x-\frac{2}{5}=\frac{3}{2} - \frac{2}{5}x + \frac{1}{10}[/tex]

[tex]\frac{2}{5}x-\frac{2}{5}= \frac{8}{5} - \frac{2}{5}x[/tex]

2x-2=8-2x

2x+2x=8+2

4x=10

x=2[tex]\frac{1}{2}[/tex]

3.   [tex]\frac{1}{3}[/tex]( [tex]x^{2}[/tex]+ x) +[tex]\frac{2}{3}[/tex]  = 2 ( [tex]\frac{2}{3}[/tex] - 2x) + 11 + [tex]\frac{1}{3}x^{2}[/tex]

[tex]\frac{1}{3} x^{2}+\frac{1}{3} x + \frac{2}{3}= \frac{4}{3} -4x+11+\frac{1}{3} x^{2}[/tex]

[tex]\frac{1}{3} x + \frac{2}{3}= \frac{4}{3} - 4x+11[/tex]

[tex]\frac{1}{3} x + \frac{2}{3} = \frac{37}{3}-4x\\[/tex]

x+2=37-12x

12x+x=37-2

13x=35

x=2[tex]\frac{9}{13}[/tex]